PENGARUH PENGGUNAAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Novianty, Yustina; Rosnita, Rosnita; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of the using Project Based Learning models on the results of learning science class V students of State Elementary School 72 West Pontianak. The method used is the experimental method. This research, using Quasi Experimental design with form Nonequivalent Control Group Design. The population in this study were all students in class V of State Elementary School 72 West Pontianak. The technique used in sample selection is simple random sampling, based on this the sample in this study is the class V B (experimental class) with the number of students namely 32 students. Data collection techniques used are direct observation techniques and measurement techniques. Data collection tools used are observation sheets and test questions. Based on the data analysis, the result of average post-test of experimental class is 76,25 and post-test of control class is 68,13, tcount 2,752 and ttable(α = 5% and dk = 32 + 32 - 2 = 62) of 1,994, because tcount>ttable, then Ha accepted. So, it can be concluded that there is the effect of the using Project Based Learning models on the results of learning. The effect size calculation obtained ES = 0,72 which is classified as medium, that is 0,2 < ES < 0,8. It can be said that project based learning model gives a considerable influence on the results of learning Science students class V of State Elementary School 72 West Pontianak. Keywords: Project Based Learning, Student Learning Result, Natural Science.